Apoptotic events induced by naturally occurring retinoids ATRA and 13-cis retinoic acid on human hepatoma cell lines Hep3B and HepG2 - Arce Vargas, Frederick (2005)
Two hepatoma cell lines were incubated for 72 h with ATRA and its analog 13cisRA and according to MTT assay, Hep3B cells were highly susceptible whereas HepG2 cells were more resistant to the treatment. At the high concentration of 166 mM, retinoids were able to induce apoptosis in both cell lines and the highest effect was observed in HepG2 cells treated with ATRA. TUNEL-based photometric ELISA showed that at the same retinoid concentration tested by flow cytometry, both cell lines showed apoptosis whereas plasma membranes were not significantly disrupted. Inhibitors of apoptosis Bcl-xL and survivin were downregulated in Hep3B cells by treatment with both retinoids. Bax, a pro-apoptotic protein, was not significantly upregulated in Hep3B cells, but was slightly increased in HepG2 cells treated with 13cisRA. Both procaspase-3 and procaspase8 were cleaved in Hep3B cells, suggesting apoptosis could be triggered through the extrinsic pathway. In the case of HepG2 cells, lack of caspase activation suggests a mechanism dependent on other kind of proteases